2012
DOI: 10.1177/147323001204000205
|View full text |Cite
|
Sign up to set email alerts
|

Social Behaviour Risk Factors for Drug Resistant Tuberculosis in Mainland China: A Meta-Analysis

Abstract: Previous treatment, poor quality DOTS, poor treatment adherence, long term illness, age 40 - 60 years and poverty are associated with a greater risk of drug resistant TB in mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 14 publications
8
46
0
3
Order By: Relevance
“…A similar report also came from mainland China (8). The 2002–2007 global survey conducted by WHO also showed that the highest prevalence of MDR-TB among newly diagnosed and previously treated TB cases was 22% and 60%, respectively (5).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…A similar report also came from mainland China (8). The 2002–2007 global survey conducted by WHO also showed that the highest prevalence of MDR-TB among newly diagnosed and previously treated TB cases was 22% and 60%, respectively (5).…”
Section: Discussionsupporting
confidence: 53%
“…The consistent findings across decades in the majority of studies and in this meta-analysis probably indicate how much the Mycobacterium TB is predisposed to develop resistance when it is exposed to anti-TB drugs. This may be related to poor patient's adherence to treatment schedule, as previous reports showed (8). …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous treatment has repeatedly been reported as the key factor contributing to the risk of MDR and XDRTB [30,31]. In the current study TB therapy in the past was the most significant risk factor for acquiring drug resistance with each additional treatment episode doubling the risk of MDR development.…”
Section: Discussionmentioning
confidence: 54%